A CONVERSATION ANALYSIS OF EFL TEACHERS’ GESTURE IN LANGUAGE ELICITATION STAGE - Wanphet, Phalangchok (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Using a Conversation Analytic (CA) method, this study explores English as a Foreign Language (EFL) teachers’ nonverbal gestures during the elicitation stage: when they elicit new words and language structures from students. In total, three hours of interactions between six EFL teachers and students during the elicitation stage in six classes are recorded and then analyzed. The teachers’ gestures are categorized according to their functions, while the classroom speech exchange, in which the EFL teachers’ gestures are identified, is examined. An analysis reveals that 1) EFL teachers’ gestures serve many pedagogical and interactional functions: managing student behavior, regulating interaction, involving students, explaining language features, evaluating students’ responses, and showing EFL teachers’ expectations for students’ language production; 2) functions of EFL teachers’ gestures sequentially correspond to the students’ responses placed on the immediate preceding turns; and 3) students not only listen to what the EFL teacher says but also interpret and later react, both verbally and nonverbally, to the teachers’ gestures. Resumen Utilizando un método de conversación analítica (CA), este estudio explora los gestos no verbales de maestros de inglés como lengua extranjera (ILE) durante la etapa de incentivación de la producción oral, cuando se incentiva el uso de nuevas palabras y estructuras lingüísticas por parte de los estudiantes. En total, se registran y después se analizan tres horas de interacción entre seis profesores y estudiantes de ILE durante su producción oral en seis clases. Los gestos de los docentes se clasifican de acuerdo con sus funciones, mientras que se examina el intercambio de discurso del aula, en el que se identifican los gestos de los profesores. El análisis revela que 1) los gestos de los docentes sirven muchas funciones pedagógicas para la interacción como: manejar el comportamiento de los estudiantes, regular la interacción, involucrar a los estudiantes, explicar las características de la lengua, evaluar las respuestas de los estudiantes, y mostrar las expectativas de los docentes para la producción de la lengua de los estudiantes; 2) las funciones de los gestos de docentes corresponden secuencialmente a las respuestas de los estudiantes colocadas en las intervenciones inmediatamente precedentes; y 3) los estudiantes no sólo escuchan lo que dice el profesor, sino que también interpretan y luego reaccionan, de forma tanto verbal como no verbal, a los gestos de los maestros.